Posthumanism in Vintage Version: Posthumanistic Concepts in Alternate History and Steampunk - Lemann, Natalia (Sensus Historiae, 2020)
The aim of this paper is analyzing trans- and posthumnanism postulates, incrypted in steampunk and alternate history novels. The author claims that novels representing above mentioned literary genres have been participating in contamporary debate, considering trans- and posthumanism ideology. Analysis of selected novels leads to the conclusion that steampunku and alternate history genres could be understand as an able to combine and discuss of transhumanism critical posthumanism ideas.